Reuse-focused selection of appropriate technologies for municipal wastewater treatment: a multi-criteria approach - Srivastava R.R.; Singh P.K. (My University, 2025)
Wastewater treatment technologies (WWTTs) are employed across the world, and the selection is mainly based on ‘past experiences’ aimed at ‘pollution prevention’ in the receiving water bodies. This paper aims to develop a methodology for the selection of an appropriate wastewater treatment chain that produces effluent suitable for the defined reuse. Adopting the least weighted cost approach, four decision criteria: Capital cost, Operation and Maintenance cost, Land requirement, and Energy requirement, have been used and the Full Consistency Method (FUCOM) has been employed for obtaining weights. Quality expectations for 14 reuses have been enlisted, and 25 WWTTs have been evaluated in a total of 360 combinations. In Kanpur city, for water reuse in industrial cooling under restricted land and challenging influent quality conditions, a combination of Membrane Bioreactor (MBR) with Wuhrmann process (WP) is obtained as the most preferred suggestion. For non-potable domestic reuse, Anaerobic Anoxic Oxic (A2O) with Ultrafiltration (UF) and Reverse Osmosis (RO) is the most preferred combination. In Varanasi city, for vehicular washing operations and for flow augmentation (inland surface water), under energy-constraint scenario, high-rate activated sludge-based biological filtration and oxygenated reactor (BIOFOR-F) is suggested. For technology supplementation to existing ASP-based STPs in the city to obtain effluent for inland surface water augmentation, WP in combination with microfiltration (MF) and reverse osmosis (RO) is suggested. Thus, the developed model may be used as a decision-making tool for planning a reuse-focused water reclamation program or for upgradation of existing STPs as per resource availability and target reuse objectives. © 2021, Islamic Azad University (IAU).